Hydrogen gas inhalation ameliorates LPS-induced BPD by inhibiting inflammation via regulating the TLR4–NFκB–IL6/NLRP3 signaling pathway in the placenta - Yafang Zhang; Xianhui Ren; Linli Zhang; Xinliu Sun; Wenjing Li; Yunxi Chen; Yan Tian; Zhongxia Chu; Youzhen Wei; Guo Yao; Yan Wang (European Journal of Medical Research, 2024)
Abstract Introduction Hydrogen (H2) is regarded as a novel therapeutic agent against several diseases owing to its inherent biosafety. Bronchopulmonary dysplasia (BPD) has been widely considered among adverse pregnancy outcomes, without effective treatment. Placenta plays a role in defense, synthesis, and immunity, which provides a new perspective for the treatment of BPD. This study aimed to investigate if H2 reduced the placental inflammation to protect the neonatal rat against BPD damage and potential mechanisms. Methods We induced neonatal BPD model by injecting lipopolysaccharide (LPS, 1 µg) into the amniotic fluid at embryonic day 16.5 as LPS group. LPS + H2 group inhaled 42% H2 gas (4 h/day) until the samples were collected. We primarily analyzed the neonatal outcomes and then compared inflammatory levels from the control group (CON), LPS group and LPS + H2 group. HE staining was performed to evaluate inflammatory levels. RNA sequencing revealed dominant differentially expressed genes. Bioinformatics analysis (GO and KEGG) of RNA-seq was applied to mine the signaling pathways involved in protective effect of H2 on the development of LPS-induced BPD. We further used qRT-PCR, Western blot and ELISA methods to verify differential expression of mRNA and proteins. Moreover, we verified the correlation between the upstream signaling pathways and the downstream targets in LPS-induced BPD model. Results Upon administration of H2, the inflammatory infiltration degree of the LPS-induced placenta was reduced, and infiltration significantly narrowed. Hydrogen normalized LPS-induced perturbed lung development and reduced the death ratio of the fetus and neonate. RNA-seq results revealed the importance of inflammatory response biological processes and Toll-like receptor signaling pathway in protective effect of hydrogen on BPD. The over-activated upstream signals [Toll-like receptor 4 (TLR4), nuclear factor kappa-B p65 (NF-κB p65), Caspase1 (Casp1) and NLR family pyrin domain containing 3 (NLRP3) inflammasome] in LPS placenta were attenuated by H2 inhalation. The downstream targets, inflammatory cytokines/chemokines [interleukin (IL)-6, IL-18, IL-1β, C–C motif chemokine ligand 2 (CCL2) and C-X-C motif chemokine ligand 1 (CXCL1)], were decreased both in mRNA and protein levels by H2 inhalation in LPS-induced placentas to rescue them from BPD. Correlation analysis displayed a positive association of TLR4-mediated signaling pathway both proinflammatory cytokines and chemokines in placenta. Conclusion H2 inhalation ameliorates LPS-induced BPD by inhibiting excessive inflammatory cytokines and chemokines via the TLR4–NFκB–IL6/NLRP3 signaling pathway in placenta and may be a potential therapeutic strategy for BPD.